Pengaruh Penggunaan Celebrity Endorser Anggun Cipta Sasmi Terhadap Brand Image Pada Iklan Produk Shampoo Pantene di Kota Denpasar - Tyas Utami Suyasa, Cok Istri Sri; Suryani, Alit (E-Jurnal Manajemen, 2014)
This study aims to investigate the influence of celebrity endorser consisting of credibility, attractiveness and meaningfulness simultaneously to the brand image in advertising products Pantene shampoo and to determine the effect of which consists of a celebrity endorser partially on brand image in ad Pantene shampoo products in the city of Denpasar. The number of samples used purposive sampling technique is based on 112 respondents. The data analysis technique used is the technique of multiple linear regression analysis. Be concluded that the results of the analysis: celebrity endorser consisting of: credibility, attractiveness and meaningfulness simultaneously and partially positive and significant impact on brand image in advertising products Pantene shampoo in the city of Denpasar. Where Anggun C. Sasmi make consumers interested in using Pantene products and make consumer products like Pantene ad is an indicator that has the most impact.   Keywords : Celebrity Endorser, Brand Image, Advertising.
Keywords: celebrity endorser, brand image, advertising